Effect of Age, Parity and Oxytocin Massage on Postpartum Mother's Milk Expenditure - Magdalena M. Tompunuh; Sri Sujawaty (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Regarding the 2016 strategic plan, which amounted to 46% through the coverage of exclusive breastfeeding for infants aged less than 6 months, 54% had reached the target. According to the province, the coverage of exclusive breastfeeding for infants aged 0-5 months ranged from 32.3% (Gorontalo) to 79.9% (East Nusa Tenggara). Through oxytocin massage, it is hoped that it can increase the hormone oxytocin for breastfeeding. The purpose of this study was to increase the production of breast milk in postpartum mothers. This type of research is a quasi-experimental pre-experiment with a one-shot case study approach in early postpartum mothers totaling 32 people by purposive sampling. The results of data analysis using the Chi Square test for univariate analysis, obtained p value = 0.757 for the age variable and p value = 0.630 for the parity variable. The results of the bivariate analysis of breast milk production found p value = 0.01 which indicates the variable of maternal comfort as indicated by p-value = 0.23. So it was concluded that there was no effect of oxytocin massage on breast milk production with indications of age and parity and the level of comfort of the mother. However, there is an effect of oxytocin massage on milk production. Abstrak: Mengacu pada renstra 2016, yang sebesar 46% melalui cakupan pemberian ASI eksklusif pada bayi usia kurang dari 6 bulan sebesar 54% telah mencapai target. Menurut Provinsi, cakupan ASI eksklusif pada bayi umur 0-5 bulan berkisar antara 32,3% (Gorontalo) sampai 79,9% (Nusa Tenggara Timur) dari 34 provinsi hanya tiga provinsi yang belum mencapai target, yaitu Gorontalo, Riau dan Kamlimantan Tengah.  Melalui pijat oksitosin diharapkan bisa meningkatkan hormon oksitosin untuk pengeluaran ASI. Tujuan penelitian ini adalah untuk meningkatkan produksi ASI pada ibu nifas. Jenis penelitian ini adalah pre eksperimen semu dengan pendekatan one shot case study pada ibu early postpartum yang berjumlah 32 orang secara purposive sampling. Hasil analisis data dengan uji Chi Square untuk analisis univariat, diperoleh p value = 0,757 untuk variable umur dan p value = 0,630 untuk variable paritas.. Adapun hasil analisis bivariate pengeluaran ASI ditemukan p value = 0,01 yang menunjukkan variabel kenyamanan ibu yang ditunjukkan dengan p value = 0,23. Sehingga disimpulkan bahwa tidak ada pengaruh pijat oksitosin terhadap produksi ASI dengan indikasi umur dan paritas dan tingkat kenyamanan ibu. Namun ada pengaruh pijat oksitosin dengan pengeluaran ASI.